Maternal Knowledge and Practices Towards Basic House Sanitation in Simeulue District - Diana Fingki; Khairunnas Khairunnas (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2022)
Basic Home Sanitation is an effort to make the house and its environment healthy. Houses with poor sanitation will facilitate the spread of infectious diseases, especially respiratory and digestive tract diseases. This study aims to assess the effect of a Mother's Knowledge about the Importance of Basic Household Sanitation on sanitation practices. The research method is a qualitative and quantitative method with a cross-sectional design. Sampling used the purposive sampling method and obtained 57 samples, namely homemakers. Data was collected using questionnaires and in-depth interviews by visiting residents' homes. Statistical analysis results show that waste management significantly affects maternal sanitation practices. While the qualitative results using NVIVO show that the people of Babul Makmur Village have a habit of managing waste by collecting waste in open trash cans. Some respondents immediately burned the garbage collected in their yards. Some throw garbage directly into the vacant land and burn it if the debris accumulates in large quantities. All wastewater generated from household activities and public bathing is discharged through sewers, leading to surrounding water bodies. we conclude that there is a need for community-based total sanitation socialization